Sustainable transformation of oil palm recyclable biomass into organic manure through vermicomposting - gawankar, m s; sumitha, s; maheswarappa, h p (Indian Horticulture, 2021)
The increasing global demand for edible oils has resulted in the increase of oil palm cultivation but there are concerns over the large amount of waste that are being generated in the field. The ability of vermicomposting process to utilize organic waste and bio-convert them into higher value added products makes it an attractive technology. The aim of this study was to investigate the characteristics and physico-chemical changes of vermicompost during composting of palm oil processed by epigeic earthworm (E. eugeniae).